Keteladanan Nabi Muhammad SAW dalam berbisnis - Ardiansyah, Muhammad Rifan (Maliki Interdisciplinary Journal, 2024)
The example of the Prophet Muhammad SAW in business presents a strong view of business ethics in Islam. The Prophet Muhammad SAW, as a successful businessman, provided an example of business ethics which is very important for Muslims. In the Islamic view, business is one of the means to achieve the benefit of society, and business ethics plays a key role in ensuring good behavior in business. Business ethics in Islam include principles such as honesty, fairness, friendliness, assistance to customers, safeguarding consumer rights, and avoiding ridiculing other people's businesses. Products sold must be halal and safe for consumers, and payment systems should be designed to facilitate transactions. The Prophet Muhammad's example in business shows that ethical business practices are important in Islam, and Islamic business ethics provide strong guidelines for good business practices in Muslim societies.